Розробка маркетингової стратегії для підвищення конкурентоспроможності структурного підрозділу ВНЗ - Юхнович, Софія; Кушнірик, Руслана (Видавництво Львівської політехніки, 2025)
The article analyzes the role of marketing strategy in enhancing the competitiveness and sustainability of university departments in the context of global changes in higher education. It emphasizes the need for a strategic, branding-oriented, and digitally driven approach to communication and positioning. Through market analysis, audience targeting, and internal resource mobilization, departments can strengthen their visibility, build long-term partnerships, and support institutional development. A well-crafted marketing strategy becomes a crucial tool for growth, reputation management, and engagement with key stakeholders, ultimately contributing to the broader appeal and success of the university as a whole.
Keywords: маркетингова стратегія; кафедра; вища освіта; брендинг; цільова аудиторія; конкурентоспроможність; освітній ринок; ВНЗ; структурний підрозділ